Targeted Therapy and Immunotherapy Response Assessment with F-18 Fluorothymidine Positron-Emission Tomography/Magnetic Resonance Imaging in Melanoma Brain Metastasis: A Pilot Study - Nguyen, Nghi C.; Yee, Melissa K.; Tuchayi, Abuzar M.; Kirkwood, John M.; Tawbi, Hussein; Mountz, James M. (Frontiers in Oncology, 2018)
Introduction This pilot study aimed at exploring the utility of the proliferation tracer F-18 fluorothymidine (FLT) and positron-emission tomography (PET)/magnetic resonance imaging (MRI) (FLT–PET/MRI) for early treatment monitoring in patients with melanoma brain metastasis (MBM) who undergo targeted therapy or immunotherapy. Material and Methods Patients with newly diagnosed MBM underwent baseline and follow-up FLT–PET/MRI scans at 3–4 weeks of targeted therapy or immunotherapy. Up to six measurable brain lesions ≥1.0 cm per subject, as identified on T1-weighted post-gadolinium images, were included for quantitative analyses. The maximum SUV of each lesion was divided by the mean SUV of the pons to obtain the SUV ratio (SUVR). Results Five enrolled subjects underwent the baseline FLT–PET/MRI study in which the MBM showed a median size of 1.7 cm (range 1.0–2.9) and increased metabolic activity with SUVR of 9.9 (range 3.2–18.4). However, only two subjects (cases #1 and #2) returned for a follow-up scan. At baseline, a total of 22 lesions were analyzed in all five subjects, which showed a median size of 1.7 cm (range 1.0–2.9) and median SUVR of 9.9 (range 3.2–18.4). At follow-up, case #1 was a 55-year-old man who received targeted BRAF inhibitor and MEK inhibitor therapy with dabrafenib and trametinib. Fused PET/MRI data of six measured lesions demonstrated a significant reduction in MBM proliferative activity (median −68%; range −38 to −77%) and size (median −23%; range −4 to −55%) at three weeks of therapy. Nevertheless, the subject eventually progressed and died 13 months after therapy initiation. Case #2 was a 36-year-old man who received immunotherapy with nivolumab and ipilimumab. The five measured MBM lesions showed a mixed response at both proliferative and morphologic imaging at 1-month follow-up. Some lesions demonstrated interval decrease while others interval increase in proliferative activity with a median −44% (range −77 to +68%). On MRI, the size change was +7% (range −64 to +50%). The therapy was switched to dabrafenib and trametinib, which led to a partial response. The patient is still alive 16 months following therapy initiation. Conclusion The five cases presented show the potential benefit of hybrid FLT–PET/MRI for the diagnosis of MBM and treatment monitoring of targeted therapy and immunotherapy. However, further studies are required to assess their complementary role in distinguishing true progression from pseudoprogression.